V-FROG—single-scan vectorial FROG. (24th June 2021) - Ilan Haham, Gil; Levin, Alexander; Sidorenko, Pavel; Lerner, Gavriel; Cohen, Oren
Abstract: We propose and experimentally demonstrate single-scan vectorial frequency-resolved optical gating (FROG) which characterizes the amplitude, phase and polarization of ultrashort laser pulses using a single measured spectrogram. It is carried out by rotating the polarization of the incoming pulse (using a half-wavelength waveplate), in parallel to scanning the delay between the pulse and its replica in an otherwise ordinary FROG apparatus. A ptychography-based phase retrieval algorithm extracts the full pulse information from the recorded spectrogram. We numerically show that this method is reliable and use it to experimentally reconstruct a pulse with intricate time-dependent polarization. We also show that this method can be used to remove time-reversal ambiguity of second harmonic generation FROG.